Performance of different fertilizers and plant spacing on the growth of mungbean - Sarker, S C; Hosen, M S; Hossain, H M M T; Roy, M; Afroz, T; Hasanuzzaman, M; Rahman, A (SAARC Journal of Agriculture, 2023)
The experiment was carried out to investigate the effect of nutrient combinations and spacing on the growth performance of mungbean (BARI mung 5) using split plot design. The experiment comprised of 3 levels of spacing; S1- 20 cm × 10 cm, S2- 30 cm × 10 cm and S3- 45 cm × 15 cm; and 6 levels of fertilizers; F0- Control (without fertilizer), F1- Recommended dose of NPK, F2- 5 t ha-1 cowdung, F3- 5 t ha-1 cowdung + Recommended dose of NPK, F4- 2.5 t ha-1 cowdung + Recommended dose of NPK and F5- 2.5 t ha-1cowdung + ½ Recommended dose of NPK. Among different treatments maximum number of leaves (13.70), branches (2.44) and dry weight (10.97g) was recorded from S3 at 60 DAS on the other hand highest number of leaves (13.83) found in F4 and dry matter (8.89g) in F3 at 60 DAS. However, when combined with fertilizers and spacings, the S3F4 treatment had the highest dry matter weight (12.7g) before harvest. In terms of yield performance, applying cowdung @ 2.5 t ha-1 along with recommended NPK resulted in the highest seed yield (1156.7 kg ha-1). The number of plant populations was higher in S2 (30 cm 10 cm) than in S3 (45 cm × 15 cm), so S2 produced the highest grain yield (1022.8 kg ha-1). It is clear that different fertilizer combinations and spacings have a significant impact on mungbean growth performance. S2F4 combinations may be the best choice for improved mungbean cultivation. SAARC J. Agric., 21(1): 189-201 (2023)